The stability of ecosystems under global environmental change - Ross, Samuel Robert (Trinity College Dublin. School of Natural Sciences. Discipline of Zoology, 2022)
Through global environmental change, humans are modifying the planet at an unprecedented rate and scale, triggering the ongoing biodiversity and climate crises. Ecological stability and the consistency of nature s contributions to people are fundamental to the continued sustainability of human societies. Stability is a complex and multidimensional concept including components such as variability in time and space and the resistance to and recovery from disturbances. Global change has the potential to destabilise ecosystems, but the form and strength of the relationship between different global change drivers and dimensions of stability remains understudied, precluding general or mechanistic understanding. Here, I combine theory, a field experiment, and observational data from a high-resolution acoustic monitoring network to reveal the potential for multiple global change drivers to erode multidimensional ecological stability. Critically, I also show how biodiversity and natural habitats can buffer the destabilising effects of global environmental change on ecosystems and soundscapes, providing vital insurance against disturbance. In an era characterised by unrelenting global change and intensifying disturbance regimes, my results provide a key step towards a generalisable understanding and ultimately management of the stability of ecosystems and their contributions to human wellbeing
APPROVED
Keywords: ecology; ecological stability; global environmental change; temporal variability; resilience; disturbance; community ecology; Anthropocene; passive acoustic monitoring; soundscape